2008
DOI: 10.1287/mnsc.1080.0927
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Spillovers in Firms: Evidence from Vehicle Emissions Testing

Abstract: In this paper, we explore how organizations influence the unethical behavior of their employees. Using a unique data set of over three million vehicle emissions tests, we find strong evidence of ethical spillovers from firms to individuals. When inspectors work across different organizations, they adjust the rate at which they pass vehicles to the norms of those with whom they work. These spillovers are strongest at large facilities and corporate chains, and weakest for the large-volume inspectors. These resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(62 citation statements)
references
References 57 publications
2
60
0
Order By: Relevance
“…However, not all employees react equally to social influences, and the question of when and why organizational environments affect employees was left unexplained by past research. This explanatory problem precluded a deeper understanding of a range of organizational phenomena, including ethical climate (Victor & Cullen, 1988), ethical culture (Treviño, 1986;Treviño et al, 1998) and conformity to (un)ethical colleagues (Gino et al, 2009;Pierce & Snyder, 2008). Our research emphasized the fact that ethical decision making occurs in the context of power differences, and identified variations in power as a parsimonious explanation for when and why organizational environments affect employees' ethical decision making.…”
Section: Theoretical Implicationsmentioning
confidence: 94%
See 3 more Smart Citations
“…However, not all employees react equally to social influences, and the question of when and why organizational environments affect employees was left unexplained by past research. This explanatory problem precluded a deeper understanding of a range of organizational phenomena, including ethical climate (Victor & Cullen, 1988), ethical culture (Treviño, 1986;Treviño et al, 1998) and conformity to (un)ethical colleagues (Gino et al, 2009;Pierce & Snyder, 2008). Our research emphasized the fact that ethical decision making occurs in the context of power differences, and identified variations in power as a parsimonious explanation for when and why organizational environments affect employees' ethical decision making.…”
Section: Theoretical Implicationsmentioning
confidence: 94%
“…For instance, we know that ethical culture may promote ethical conduct (Treviño et al, 1998), but we do not know when and why it does so. We also know that unethical coworker conduct may lead employees to behave more unethically (Ashforth & Anand, 2003;Pierce & Snyder, 2008), but we do not know when and why this actually happens. In the following section, we develop a theoretical model explaining how decision-maker's social power and self-focus can help answer these questions.…”
Section: Ethical Decision Making In Organizational Contextsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Carpenter, Matthew, and Schirm (2010) found that sabotage among coworkers is higher in tournaments than it is under piece-rate compensation. Pierce and Snyder (2008) showed that unethical conduct by automobile inspectors is influenced by the presence of unethical conduct in the organization where those inspectors work. Related research conducted in laboratory settings examines how individuals' unethical behavior often arises through vertical specialization, which diffuses the responsibility for behaving unethically (Ellman and Pezanis-Christou, 2010;Hamman, Weber, and Loewenstein, 2010).…”
Section: Relevant Literature and Hypothesesmentioning
confidence: 99%